3D simulation of deflection basin of pavements under high-speed moving loads. (30th November 2019) - Deng, Yong; Luo, Xue; Gu, Fan; Zhang, Yuqing; Lytton, Robert L.
Highlights: Characteristics of deflection basins under high-speed moving loads are revealed. A new structural parameter termed lag angle for pavement structures is identified. The lag angle is found to be closely related to phase angle of viscoelastic materials. The moving deflection basins from FE models match well with field measurements. The 3D FE models fulfill the expensive and limited high-speed field measurements. Abstract: The nondestructive testing of pavements currently has become more focused on continuous deflection profiles and vehicle moving speeds, which are recognized to be critical in obtaining complete and accurate pavement responses and conditions. However, current techniques cannot produce satisfactory results in terms of continuous deflection profiles at high-speed moving loads. Under this circumstance, the computational simulation is a good alternative. The objective of this study is to utilize the three-dimensional (3D) finite element (FE) analysis to investigate the characteristics of deflection basins of pavements under high-speed moving loads. Specifically, a 3D FE pavement model is constructed with six sets of pavement materials representing six types of pavements and four moving speeds (24 km/h, 40 km/h, 64 km/h, and 80 km/h). The results demonstrate that the deflection basin of a pavement exhibits an asymmetric shape under a high-speed moving load. It also reveals that there is a time lag between the maximum deflection and the center of the load in flexible pavements. This time lag is utilized to define a new term of "lag angle". The effects of the material viscoelasticity, structural inertia damping, moving speed, and pavement deterioration conditions on the shape and lag angle of the deflection basin are illustrated. Furthermore, it is found that the lag angle of the deflection basin is closely related to the phase angle of the viscoelastic pavement materials. Finally, the deflection basins predicted by the 3D FE analysis are proven to be comparable to the field deflections obtained at a high moving speed.